Design and Implementation of a Platform for Controlling the Mentor Robotic Arm - Rosa, Luana; Cunha, Mauro; Moraes, Fabiano (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
This work presents the design and implementation of a platform (hardware and software) for controlling the Mentor robotic arm. Initially, power and data acquisition systems were designed and implemented. In the sequence, the software for communication between the computer and the manipulator was developed, as well as a human-machine interface for the system. The Arduino Mega 2560 was used for hardware control and firmware storage. Experimental results prove the proposed system can be used for robot online programming as well as for the implementation of various control laws, allowing the use of the system in various disciplines of the area of control and automation.